77 Medical maximizing-minimizing and patient preferences for high and low-benefit care, perceived acceptability of recommendations against low-benefit care, and patient satisfaction. (4th December 2019) - Scherer, Laura; Shaffer, Victoria; DeWitt, Jeffrey; Caverly, Tanner; Zikmund-Fisher, Brian
Abstract : Objective: The Medical Maximizer-Minimizer Scale (MMS) assesses patient preferences for active vs. passive approaches to healthcare and predicts healthcare utilization and patient preferences in a variety of healthcare contexts. In two surveys, our objective was to determine the utility of the MMS for predicting patient preferences for both high and low-benefit care, the acceptability of recommendations related to low-benefit care, and patient satisfaction with their physician. Methods: We conducted two online U.S. surveys, totaling 1, 576 men and women age 18–84 (M=34; 52, both samples were majority White). The MMS was associated with the following outcomes: In Survey 1, participants indicated their medical preferences in 18 health scenarios that were constructed using medical expertise and Choosing Wisely ® recommendations. In 8 scenarios the optimal approach was active intervention (e.g., colonoscopy at age 60) and in 10 scenarios an active intervention was not optimal (e.g., full body CT scan in an asymptomatic healthy person). In Survey 2, participants indicated (1) whether they think too much medicine is a problem, (2) the acceptability of recommendations to take a less aggressive approach to imaging for low back pain and colorectal cancer screening in older adults, (3) their satisfaction with their primary physician, and (4) their perception of whether their physician is a minimizer or maximizer. Results: In Survey 1, MMS scores were significantly correlated with medical preferences in 16/18 scenarios ( r s=.16-.39, p s≤.001). Maximizers were more likely than minimizers to want to receive active medical intervention across the 8 scenarios in which action was appropriate ( r =.35, p<.001) and across the 10 scenarios for which action was inappropriate ( r =-.57, p<.001). In Survey 2, maximizers were less likely than minimizers to believe that too much medicine is a problem (r=-.37, p<.001), and were less likely to believe recommendations about back imagining and colorectal cancer screening are acceptable (rs=-.34, -.36 respectively, both ps<.001). Maximizers were slightly more satisfied with their primary physician than minimizers (r=.10, p=.007) but the perceived agreement between one's own MMS score and one's physician's maximizing-minimizing orientation was more strongly predictive of patient satisfaction (r=-.27, p<.001). Conclusions: Relative to minimizers, maximizers are more likely to prefer both high-benefit and low-benefit care and are more likely to believe that recommendations to take a less aggressive approach to testing are unacceptable. Maximizers may therefore be at risk for overutilizing low-value care (while minimizers may be at risk of underutilization). As a result, the MMS may be useful for targeting interventions to encourage appropriate use. The perceived match between patients' and physicians' maximizing-minimizing orientation may also have implications for patient satisfaction and shared decision making.